2020
DOI: 10.1097/sap.0000000000002298
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic Wall Reconstruction

Abstract: Introduction The reconstruction of defects in thoracic wall remains a challenge for plastic surgeons. Advances in surgical treatment of illnesses of thoracic wall have been fostering the treatment of lesions within more advanced levels. Consequently, larger and more complex defects are generated, demanding soft tissue covering and framework repair. Objective The aim of this study was to report the experience in chest wall reconstruction and demographics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In 35 procedures on 30 patients, a total of 35 complications occurred, resulting in a relative overall complication rate of 100% (37% major and 63% minor). Contrasting this and having used mainly pedicled latissimus dorsi flaps, Groth et al reported an overall complication rate of 50% (12.5% major and 37.5% minor complications) in a more than decade younger collective of 32 patients with mainly oncologic reconstructions [15]. In their definition of major complications, compared to our results, only complications requiring surgical procedures were considered.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…In 35 procedures on 30 patients, a total of 35 complications occurred, resulting in a relative overall complication rate of 100% (37% major and 63% minor). Contrasting this and having used mainly pedicled latissimus dorsi flaps, Groth et al reported an overall complication rate of 50% (12.5% major and 37.5% minor complications) in a more than decade younger collective of 32 patients with mainly oncologic reconstructions [15]. In their definition of major complications, compared to our results, only complications requiring surgical procedures were considered.…”
Section: Discussionmentioning
confidence: 51%
“…While the first approach to chest wall reconstruction with a pedicled latissimus dorsi flap was delineated by Purpura in 1908, the reconstructive surgeon's toolbox has since evolved notably [14]. Despite a considerably high morbidity and mortality attributable to these complex operations, reconstruction has been shown to have a reasonable long-term survival while being safe and effective [9,15]. Many authors have put forth and adapted treatment algorithms for chest wall defects [5,12,16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 9 For these defects, musculocutaneous flaps perfused by large vessels, can increase the blood supply to the defects, fill the cavity, and cover the wounds. 10 Among these, the LD flap has been greatly applied.…”
Section: Discussionmentioning
confidence: 99%